The conduct of science practical for working adults in an ODL setting - Santhanadass, Thangapragasam; Rajesh Kumar, P. (2011)
Laboratory practical play an important role in the teaching and learning of science and engineering courses. They are indispensable in elucidating and verifying the fundamental scientific principles taught in the class-room. By reinforcing the fundamental concepts and laws through laboratory experiments, practical sessions facilitate the learning process and widen the student’s understanding of science and engineering. Achievement of scientific proficiency cannot be achieved without laboratory practical experience. Besides, they also promote critical skills such as report writing, data handling, and the ability to interpret and evaluate evidence. In this paper, we review the science practical sessions for working adults in the context of open and distance learning. We share our experiences and discuss how the practical science sessions were conducted successfully nationwide to cater to the needs of adult learners enrolled in the Bachelor of Education (Science) programme at Open University Malaysia. Besides this, we will also elaborate on some of the pertinent issues and challenges that were faced in conducting these practical sessions over the last 8 years. (Abstract by authors)